Exploring the Impact of Store Attributes on Brand Loyalty through the Omni-Channel Experience and Brand Love - Mukhsin, M.; Kustiawan, Unggul (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
The purpose of this study is to explore the factors influencing offline store attributes and online store attributes on brand loyalty through omni-channel experience and brand love, focusing on Chinese smartphone brands in Indonesia among Generation Z and Millennial consumers. The research data were collected using a survey method through the online distribution of questionnaires to 150 respondents, of which 127 completed responses were used as the study sample. Data analysis was conducted using factor analysis and structural equation modeling (SEM) with SmartPLS software. The strength of this study lies in its omni-channel context, which integrates both online and offline dimensions. The results show that both offline and online store attributes positively influence omni-channel experience, brand love, and brand loyalty. Brand love further strengthens brand loyalty. Offline and online store attributes serve as key drivers of omni-channel experience, which enhances brand love and ultimately leads to brand loyalty (R² = 77.2%). Omni-channel experience partially mediates the relationship between offline store attributes and brand love, while fully mediating the relationship between online store attributes and brand love. Managerial implications for enhancing brand loyalty include providing responsive service, maintaining store cleanliness and neatness, and ensuring that online systems facilitate easy access to and comparison of a wide range of products. Furthermore, the strategy for enhancing the omni-channel experience is focused on strengthening offline and online store attributes through the provision of a comprehensive product assortment and quality that meets customer expectations.